MEANINGFUL LEARNING: THE MAIN CONSTITUTIVE AND CONSECUTIVE COMPONENTS AND THEIR PRESENCE IN SCIENCE TEACHING - Abu-Ghaneema, Elias (Rocznik Pedagogiczny, 2018)
This pilot study aims to identify the presence of components which are consistent with meaningful learning in science teaching. Semi-structured interviews were conducted with six science teachers and the results show that some of the teachers’ perceptions and practices in science teaching are consistent with meaningful learning components. Science teachers’ descriptions led to the identi- fication of six categories which can be classified into two sets of components: Constitutive (e.g., ‘authenticity’ and ‘prior knowledge’) and. Consecutive (e.g., ‘cooperative learning’, ‘knowledge construction’, ‘learning by doing’ and ‘feedback’). Based on these results, it can be concluded that there is a positive change in teachers’ perceptions and implementation of pedagogical processes for promoting meaningful learning in science teaching. The implications of these findings for future research are discussed.